Reproduction and long-term monitoring of drying of mudbricks and small mudbrick walls for the preservation of the ancient mudbrick wall of Eleusis - Bardanis Michail; Marinis Theodoros; Toumbakari Eleni-Eva; Dounias Georgios (E3S Web of Conferences, 2023)
The mudbrick wall remains preserved to date in the site of Eleusis are some of the largest preserved in Greece. Following an extensive investigation of the properties of existing mudbricks, material of similar properties from the archaeological site of Eleusis was used to reproduce mudbricks of similardensity with the ancient ones after drying with various concentrations of dry grass also from the archaeological site. Actual mudbricks were reproduced and brought to a final equilibrium condition under climatic conditions practically similar to those in Eleusis. Others were used to trim samples and measuremechanical properties to compare with original mudbricks, others were instrumented with suction and volumetric water content sensors in order to monitor mudbrick drying under climatic conditions and others in order to build small mudbrick walls with mortar from the same soil used to make the mudbricks. These small mudbrick walls included the mudbricks with internally installed suction and volumetric water content sensors and were also constructed with similar sensors in the mortar. This allowed monitoring of drying of the mortar until each whole mudbrick wall came to equilibrium and was then subjected to uniaxial compression under load control. Monitoring of mudbricks and mudbrick walls indicated that the higher the dry grass concentration, the higher the drying rate of the mudbricks; the lower the dry grass concentration the higher the probability of mudbrick cracking during drying; minimum required time for mudbrick and mudbrick wall drying for the particular soil used in the ancient mudbricks is not less than 5 weeks. Finally, uniaxial compression under load control on both samples trimmed from dried mudbricks and mudbrick walls indicated that uniaxial compression strength decreases with increasing dry grass concentration and mudbrick wall strength should be expected in the order of 70-80% that of the cubic samples trimmed from dried mudbricks and subjected to load rate control compression.